Proceedings of the Fourth International Symposium on Block and Sublevel Caving 2018
DOI: 10.36487/acg_rep/1815_0.1_campbell
|View full text |Cite
|
Sign up to set email alerts
|

Optimising for success at the Grasberg Block Cave

Abstract: At PT Freeport Indonesia's Grasberg mining complex, the Grasberg open pit is scheduled to cease production in early 2019. Mining of the Grasberg deposit will then transition to the underlying Grasberg Block Cave (GBC) mine, with initial undercutting currently planned for late 2018. The GBC is projected to become the district's flagship underground mine for the next two decades. Early-stage production areas at the GBC are hosted within a heterogeneous rock mass. The footprint will be subjected to variable abutm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Prior to undercutting, a number of mine-scale design changes were implemented based on an improved understanding of geological and stress conditions (Campbell et al 2018). Specific to the undercut and extraction levels, changes focused mainly on undercut and development sequencing, the prioritisation of various blocks within the footprint and the transition from pit operations.…”
Section: Ground Support and Pillar Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Prior to undercutting, a number of mine-scale design changes were implemented based on an improved understanding of geological and stress conditions (Campbell et al 2018). Specific to the undercut and extraction levels, changes focused mainly on undercut and development sequencing, the prioritisation of various blocks within the footprint and the transition from pit operations.…”
Section: Ground Support and Pillar Performancementioning
confidence: 99%
“…The diorite is typically massive to semi-massive characterized by poorly developed jointing and moderate vein intensity. The mean intact strength of the diorite is approximately 110 MPa (Campbell et al 2018). Field and laboratory observations at the GBC have recently shown that veining plays a key role in rock mass strength reduction (Bewick et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Geological condition is one of the key parameters of developing drifts in the GBC due to a wide range of complex lithological units dominated by tertiary dioritic-monzonitic intrusions of Grasberg Igneous Complex and sedimentary country rocks associated with strike-slip faulting (Campbell et al 2018). This complex lithology condition, combined with geological structures, results in poor and very poor ground conditions in several areas including the Drainage Drift 4 (DD4).…”
Section: Introductionmentioning
confidence: 99%
“…Both mines have broken through into overlying mines with GBC into the GRS and DMLZ into the Deep Ore Zone (DOZ) panel cave mine. Although the GBC and DMLZ both face their own challenges due to nature of mass mining, style of deposits, interactions with overlying mines and location in mountainous terrain with high rainfall, both mines share a common challenge related to oversize and fines management (Campbell et al 2018;Nugraha et al 2020;Priatna et al 2020).…”
Section: Introductionmentioning
confidence: 99%